Does Affect Voluntary significant to non-profit servant motivation in Yogyakarta? - Dian Suluh Kusuma Dewi; Achmad Nurmandi; Dyah Mutiarin (Universitas Muhammadiyah Tangerang, 2020)
The implications of prosocial behaviour on public service motivation are found. The link between prosocial behaviour and public service motivation from a sense of wanting to help others. In practice, civil servants are often encouraged to help the community. The meeting point between public service motivation and prosocial behaviour is with the choice to become a volunteer. Civil servants who have a robust public service motivation will be involved in voluntary activities. This study aims to examine the effect of volunteerism on the motivation of public services on civil servants in Yogyakarta special government. The method used in this research is quantitative research methods. Questionnaires are distributed at special local government offices in Yogyakarta that provide basic services. The number of respondents who answered the survey was 321 people. Data processing using SEM PLS and data analysis using quantitative descriptive. The results of this study are prosocial behaviour and the value of altruism through voluntarism activity significantly influence the motivation of public services. But directly, prosocial and altruism do not affect public service motivation. Perilaku prososial berimplikasi terhadap motivasi pelayanan publik. Hubungan antara perilaku prososial dan motivasi pelayanan publik timbul dari rasa ingin membantu orang lain. Dalam praktiknya, pegawai negeri sering didorong untuk membantu masyarakat. Titik temu antara motivasi pelayanan publik dan perilaku prososial adalah dengan pilihan untuk menjadi sukarelawan. Pegawai negeri yang memiliki motivasi pelayanan publik yang kuat akan terlibat dalam kegiatan sukarela. Penelitian ini bertujuan untuk menguji pengaruh kesukarelaan terhadap motivasi pelayanan public pada pegawai negeri sipil di Daerah Istimewa Yogyakarta. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif. Kuisioner disebar di kantor-kantor pemerintah Daerah Istimewa Yogyakarta yang menyediakan layanan dasar. Jumlah responden yang mengisi survei adalah sebanyak 321 orang. Pengolahan data menggunakan SEM PLS dengan teknik analisis data deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa perilaku prososial dan nilai altruisme melalui aktivitas voluntarisme berpengaruh signifikan terhadap motivasi pelayanan publik. Tetapi, prososial dan altruisme tidak secara langsung memengaruhi motivasi pelayanan publik.